338 APOPTOSIS AND CHROMATIN STRUCTURE ARE ALTERED IN HIPPOCAMPAL CELLS OF PRETERM LAMBS MANAGED BY MECHANICAL VENTILATION FOR 3 DAYS. Issue 1 (1st January 2007) - Alvord, J.; Dahl, M. J.; Callaway, C.; McKnight, R. A.; Null, D.; Yoder, B.; Lane, R. H.; Albertine, K. H.
Abstract : Objective: Mechanical ventilation (MV) of the premature human neonate is associated with brain injury. In preterm lambs, we have shown that MV injures the hippocampus. In other models, our group has shown that hippocampal injury is associated with epigenetically determined changes in gene expression. We hypothesized that histone acetylation and methylation in the hippocampus will be affected by MV of preterm lambs. Materials/Methods: Preterm lambs (≈132 days' gestation; term ≈148 days), treated with antenatal steroids and postnatal surfactant, were managed by MV or nasal continuous positive airway pressure (nasal CPAP) ( n = 4 each). Fetal lambs served as gestation controls ( n = 4). At the end of 3 days, the hippocampus was isolated and analyzed by immunoblot for cleaved caspase 3 (apoptosis) and acetylated H3K9, dimethyl H3K4, and trimethyl H3K4 (histone modification). Results: Homogenates of the hippocampus of the MV group had significantly more cleaved caspase protein abundance and acetylated H3K9, dimethyl H3K4, and trimethyl H3K4 protein abundance than the nasal CPAP and the fetal control groups. Conclusion: Management of preterm lambs with MV leads to moderate ischemia of the brain, as evidenced by increased apoptosis, as well as hippocampal vulnerability to altered chromatin structure. Based on the chromatin structure results, we speculate that a specific subset of genes is expressed in the hippocampus due to MV-mediated changes in intrathoracic pressure and limited cerebral vascular autoregulation in the premature newborn. HL62875, HL56401, HD41075, CHRC.